Pengaruh Variasi Surfaktan terhadap Struktur, Morfologi, dan Aktivitas Katalitik TiO₂ Mesopori yang Disintesis dengan Metode Kopresipitasi - Aswin; Sarinah Pakpahan; Rimawanto Gultom (Progressive Physics Journal, 2025)
This study examines the effect of different surfactants: Cetyltrimethylammonium Bromide (CTAB), Didodecyldimethylammonium Bromide (DDAB), and Methyltrioctylammonium Bromide (MTAB) on the synthesis of mesoporous TiO2 using the co-precipitation method. Characterization was performed using Raman Spectroscopy, BET (Brunauer-Emmett-Teller) surface area measurement, Differential Scanning Calorimetry (DSC), and X-ray Diffraction (XRD) techniques. The results indicate that the highest surface area was achieved by CTAB 98.32 m2/g, while MTAB yielded the greatest pore volume 0.2517 cc/g and the largest average pore diameter 10.498 nm. Furthermore, a simple catalytic activity test was performed through the degradation of methylene blue under UV irradiation, which showed that the TiO2–MTAB sample had the highest degradation rate of 0.032 min-1. This indicates a positive correlation between pore size and photocatalytic efficiency.